Family emotional communication in caring for patients with Covid-19 at Home: Personal experience and story - Astuti, Agnes Dewi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2022)
This photo essay pictures my journey as temporary head of the family in creating good and conducive conditions for all family members during Covid-19 outbreak. Family emotional communication is important in building resilience and strength in dealing with how we live in one roof when one or two of the family members diagnosed with Covid-19. We suffered anxiety and depression during the home isolation. For that, I have to implement peaceful communication, with correct information and ensure that these conditions are things that must be lived together, so that openness is needed for all families about what they feel, what they think, what they want, and what is needed because a disease pandemic situation that affects people's psychology widely and massive, starting from the way of thinking in understanding information about health and illness, changes in emotions (fear, worry, anxiety) and social behavior (avoidance, stigmatization, healthy behavior). We also optimise the chatting application to communicate, and share our updates with the other loving family members and friends. The current condition has changed, after all family members are declared healthy and with a new order in society, we are jointly committed to sticking to health protocols at home, for example always wearing masks and face shields, always washing hands diligently, maintaining distance. all done with sincerity and joy, because it is a must so that all family members can stay healthy. All my family activities inside the house and outside the house, still pay attention to and apply health protocols. The past experience is a valuable experience for us as a family, so that we always pay attention to personal health, family and the environment around them. The family always maintains interpersonal communication, is mutually responsible for maintaining personal and family hygiene with a healthy lifestyle, and is open in communicating all problems that exist in the family. Through the ability to communicate emotions, families are expected to strengthen each other so that they can survive the covid-19 pandemic together.